Evaluating the Performance of a Novel Digital Slippage System for Tractor Wheels Across Varied Tillage Methods and Soil Textures - Ahmed Abed Gatea Al-Shammary; Andrés Caballero-Calvo; Jesús Fernández-Gálvez (Agriculture, 2024)
Accurate measurement of slip rate (SR) in agricultural tractors, particularly in Iraq, is essential for optimizing tractive efficiency, fuel economy, and field efficiency. Presently, tractors in Iraq lack sensors for SR detection, posing a challenge. This research addresses the issue by introducing a wireless technology, the novel digital slippage system (NDSS), designed to precisely measure the SR of rear wheels. The NDSS was tested across diverse field conditions, involving six soil textures and various kinds of agricultural tillage equipment (A-TE). Different tillage practices, including conservational tillage (CT) with a chisel plough, traditional tillage (TT) with a moldboard plough and disc plough, and minimum tillage (MT) using disc harrowing and spring tooth harrowing, were examined. Results from the NDSS were compared to traditional techniques, demonstrating the cost effectiveness and overall performance. Silty loam soil exhibited higher SR values, while the silty clay soil showed lower values. SR varied significantly across soil textures, with more cohesive soils leading to reduced SR percentages. Additionally, tillage methods had a marked influence on SR values. The use of CT resulted in higher SR values of 18.35% compared to TT and MT systems, which recorded lower SR values of 13.69% and 6.03%, respectively. SR measurements were also found to be affected by the draft force during the loading of A-TE, emphasizing the role of operational conditions in tractor performance, especially in challenging field environments. Comparison between NDSS and traditional techniques revealed that the NDSS offered high accuracy, flexibility, configurability, and consistent performance. The NDSS demonstrated superior precision, making it an effective tool for assessing SR in agricultural tractors.